2022
DOI: 10.5812/ijpr.123949
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Properties of the Genus Symphytum L.: A Review

Abstract: : The Symphytum genus has been mainly used in traditional medicine, containing its anti-inflammatory activity. Symphytum spp.’s active components, such as allantoin, polyphenols, flavonoids, and alkaloids, can act on several intentions in the signaling pathway, constrain pro-inflammatory enzymes, reducing the construction of inflammatory chemokine’s and cytokines, and decreasing oxidative stress, which afterward suppresses inflammation procedures. Preclinical and clinical trials have reported the prevailing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 113 publications
0
2
0
3
Order By: Relevance
“…Studies have shown that rosmarinic acid can reduce oxidative stress and inhibit the production of inflammatory cytokines in the skin, leading to improved skin health [43]. Comfrey also contains tannins and pyrrolizidine alkaloids, which contribute to its anti-inflammatory and wound-healing effects [44][45]. (4) S. dulcamara stems have been traditionally employed in folk medicine as a narcotic agent and as a remedy for conditions such as rheumatism, migraine, and severe inflammation [91].…”
Section: Taraxacum Officinale Web Family -Compositaementioning
confidence: 99%
“…Studies have shown that rosmarinic acid can reduce oxidative stress and inhibit the production of inflammatory cytokines in the skin, leading to improved skin health [43]. Comfrey also contains tannins and pyrrolizidine alkaloids, which contribute to its anti-inflammatory and wound-healing effects [44][45]. (4) S. dulcamara stems have been traditionally employed in folk medicine as a narcotic agent and as a remedy for conditions such as rheumatism, migraine, and severe inflammation [91].…”
Section: Taraxacum Officinale Web Family -Compositaementioning
confidence: 99%
“…Der Nachweis der PAs Symlandin und Echimidin weist auf eine Verfälschung mit anderen Symphytum-Arten hin 7 14 . In Wurzeln wurden 1380–8320 μg PAs pro Gramm nachgewiesen, in Blättern 15–55 μg PAs/g 7 14 34 .…”
Section: Beinwell-inhaltsstoffeunclassified
“…2,1 % gemessen [24]. Symphytum-Kraut enthielt im Mittel 9,4 mg Allantoin pro Gramm, die Wurzel 25,8 mg/g [34]. Nach Entfernung des Schleims kam es zu einem Anstieg der Rosmarinsäure, von Globoidnan A, Globoidnan B und Rabdosiin.…”
Section: Beinwell-inhaltsstoffeunclassified
See 1 more Smart Citation
“…Comfrey also contains tannins and pyrrolizidine alkaloids, which contribute to its anti-inflammatory and wound-healing effects [ 342 , 343 ].…”
Section: Introductionmentioning
confidence: 99%